Acceptorless Dehydrogenation of Alcohols on a Diruthenium(II,II) Platform - Dutta, Indranil; Sarbajna, Abir; Pandey, Pragati; Rahaman, S. M. Wahidur; Singh, Kuldeep; Bera, Jitendra K (Organometallics, 2016)
The diruthenium(II,II) complex [Ru2(L1)(OAc)3]Cl (1), spanned by a naphthyridine-diimine ligand and bridged by three acetates, has been synthesized. The catalytic efficacy of complex 1 has been evaluated for the acceptorless dehydrogenation (AD) of alcohols and for the dehydrogenative coupling reactions of alcohols with Wittig reagents. The diruthenium(II,II) complex is an excellent catalyst for AD of a diverse range of alcohols, and it is shown to be particularly effective for the conversion of primary alcohols to the corresponding aldehydes without undesired side products such as esters. Triphenylphosphonium ylides in a one-pot reaction with alcohols afforded the corresponding olefins in high yields with excellent E selectivity. The liberated dihydrogen gas was identified and measured to be 1 equiv with respect to alcohol. Deuteration studies with PhCD2OH revealed the absence of isotope scrambling in the product, indicating the involvement of a Ru-monohydride intermediate. Kinetic studies and DFT calculations suggest a low-energy bimetallic β-hydride elimination pathway where rate-limiting intramolecular proton transfer from alcohol to metal-bound hydride constitutes the dehydrogenation step. The general utility of metal–metal bonded compounds for alcohol AD and subsequent coupling reactions is demonstrated here.